Employment Patterns of Husbands and Wives and Family Income Distribution in Italy (1977-1998) - Daniela Del Boca; Silvia Pasqua (Institute for the Study of Labor (IZA), 2002)
The pattern of employment among men and women has changed remarkably over the past decades. While the employment rate of women has risen, that of men has continued to decline. Disproportionate growth in the participation in the labor market of women with highincome husbands has heightened concerns that wives? earnings may increase income inequality among married couples. Questions about the implications for income distribution have also been raised, especially in countries like Italy, the UK, and the US, where more noticeable growth of income inequality during the last decade has accompanied changes in employment levels. In this paper we attempt to measure the impact of the changes of women and men?s employment patterns on the distribution of income among Italian households. Using microdata from the Historical Archive of the Bank of Italy Survey of Household Income and Wealth (SHIW), a repeated cross-sectional survey that covers the period 1977-1998, we examine the impact of employment changes on inequality in family income distribution and how this relationship has changed over time and across regions. Our preliminary results show that the increase in the employment of women during the period of observation had the effect of reducing inequality in family incomes, while the decline in men's employment had the opposite effect. The equalizing impact of wives' work on income inequality has become increasingly important over time and has been greater among Northern households. Especially since the mid-nineties, wives' earnings have reduced inequality in as much as the distribution of income would have been less equal in their absence. More conclusive results could be achieved by analyzing a more structural approach where the labor supply of husbands and that of wives are determined simultaneously.
Keywords: D31; J22; 330; labor market participation; family income inequality; Erwerbstätigkeit; Geschlecht; Frauenerwerbstätigkeit; Haushaltseinkommen; Einkommensverteilung; Arbeitsangebot; Italien